Tuning optical properties of perovskite nanocrystals by supermolecular mercapto-β-cyclodextrin. Issue 83 (30th September 2016) - Li, Qi-Le; Lu, Wen-Xiu; Wan, Neng; Ding, Shou-Nian
Abstract : This study reports a host–guest interaction strategy for systematically manipulating the optical properties of cesium lead halide perovskite nanocrystals (CsPbBr3 NCs) by protectant-mediated mercapto-β-cyclodextrin (SH-β-CD). Abstract : This study reports a host–guest interaction strategy for systematically manipulating the optical properties of cesium lead halide perovskite nanocrystals (CsPbBr3 NCs) by protectant-mediated mercapto-β-cyclodextrin (SH-β-CD). The fluorescence of CsPbBr3 NCs can be adjusted over 405–510 nm with the quantum yields (QY) maintained at 50–90%.